1998
DOI: 10.1113/expphysiol.1998.sp004148
|View full text |Cite
|
Sign up to set email alerts
|

Thermoregulatory responses of the newborn pig during experimentally induced hypothermia and rewarming

Abstract: SUMMARYExposure to a temperature of 14°C was used to induce a progressive hypothermia in fourteen conscious newborn piglets. Heat production, body (rectal) and skin (between the shoulders) temperatures and shivering intensity assessed as the electromyographic activity (EMG) of longissimus thoracis muscle were measured until body temperature reached 30°C and during a recovery period of 2 h at an ambient temperature of 24°C (n = 7) or 34°C (n = 7). During body cooling, heat production increased up to 9.67 + 1 28… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 14 publications
(25 reference statements)
2
27
0
Order By: Relevance
“…The lowest RT was measured 30 min after birth in the present study, corresponding to the time frame found in previous studies with air temperature around 20°C (Malmkvist et al, 2006;Pedersen et al, 2013). RT_0.5 h in CG (34.3°C) was close to the lower limit (~34°C) where thermoregulatory responses and carbohydrate metabolism are seriously impaired (Lossec et al, 1998). Adding radiant heat at the birth place reduced the drop in RT_0.5 h, even though the piglets left the heated zone after 11.4 min on average.…”
Section: Effect Of Treatmentsupporting
confidence: 81%
See 1 more Smart Citation
“…The lowest RT was measured 30 min after birth in the present study, corresponding to the time frame found in previous studies with air temperature around 20°C (Malmkvist et al, 2006;Pedersen et al, 2013). RT_0.5 h in CG (34.3°C) was close to the lower limit (~34°C) where thermoregulatory responses and carbohydrate metabolism are seriously impaired (Lossec et al, 1998). Adding radiant heat at the birth place reduced the drop in RT_0.5 h, even though the piglets left the heated zone after 11.4 min on average.…”
Section: Effect Of Treatmentsupporting
confidence: 81%
“…The extent of the initial drop and the rate of the subsequent rise depend on the external environment (Le Dividich and Noblet, 1981;Malmkvist et al, 2006;Pedersen et al, 2013) and are negatively correlated to the chance of survival of the piglets (Tuchscherer et al, 2000;Baxter et al, 2009;Pedersen et al, 2011). The first critical step to avoid hypothermia is to reduce the initial fall in RT as much as possible (Lossec et al, 1998). The lowest RT was measured 30 min after birth in the present study, corresponding to the time frame found in previous studies with air temperature around 20°C (Malmkvist et al, 2006;Pedersen et al, 2013).…”
Section: Effect Of Treatmentsupporting
confidence: 61%
“…Some degree of relationship between indoor and outdoor temperatures was expected for both rooms. However, low temperature levels such as the average 15.6 °C found at the crate level in Room 1 were not expected and are a dangerous risk for the survivability of piglets, as they are poorly insulated at birth, and thus subject to cold stress (Lossec et al, 1998). Crates with temperatures of 15.6 °C or below were found to be located below attic inlets, which suggests that air from the attic inlets was flowing directly towards the animals, instead of properly mixing with the indoor air first before reaching them.…”
Section: Resultsmentioning
confidence: 99%
“…Keeping sows and piglets within their thermal comfort zones in conventional farrowing crates is challenging, even in thermally controlled environments, as sows can be heat stressed above 22 °C (Quiniou and Noblet, 1999), whereas piglets feel comfortable within the range of 29.0 °C to 34.0 °C (Johnson and Marchant-Forde, 2009;Lossec et al, 1998;Renaudeau et al, 2003). While heat stressing sows has negative behavioral, physiological and productivity consequences (Quiniou and Noblet, 1999;Renaudeau and Noblet, 2001), piglets commonly experience a 2.0 °C to 4.0 °C drop in body temperature at High relative humidity reduces the efficiency of heat loss through evaporation and adds heat to the air, all of which can contribute to pig heat stress when combined with high ambient temperatures.…”
Section: Relative Humidity -Within Day and Within Room Variationmentioning
confidence: 99%
See 1 more Smart Citation